PXR Ablation Alleviates Diet-Induced and Genetic Obesity and Insulin Resistance in Mice - He, Jinhan; Gao, Jie; Xu, Meishu; Ren, Songrong; Stefanovic-Racic, Maja; O'Doherty, Robert Martin; Xie, Wen (Diabetes (New York, N.Y.), 2013)
The pregnane X receptor (PXR), along with its sister receptor constitutive androstane receptor (CAR), was initially characterized as a xenobiotic receptor that regulates drug metabolism. In this study, we have uncovered an unexpected endobiotic role of PXR in obesity and type 2 diabetes. PXR ablation inhibited high-fat diet (HFD)–induced obesity, hepatic steatosis, and insulin resistance, which were accounted for by increased oxygen consumption, increased mitochondrial β-oxidation, inhibition of hepatic lipogenesis and inflammation, and sensitization of insulin signaling. In an independent model, introducing the PXR−/− allele into the ob/ob background also improved body composition and relieved the diabetic phenotype. The ob/ob mice deficient of PXR showed increased oxygen consumption and energy expenditure, as well as inhibition of gluconeogenesis and increased rate of glucose disposal during euglycemic clamp. Mechanistically, the metabolic benefits of PXR ablation were associated with the inhibition of c-Jun NH2-terminal kinase activation and downregulation of lipin-1, a novel PXR target gene. The metabolic benefit of PXR ablation was opposite to the reported prodiabetic effect of CAR ablation. Our results may help to establish PXR as a novel therapeutic target, and PXR antagonists may be used for the prevention and treatment of obesity and type 2 diabetes.